Identification Geodiversity Hotspots Using Grid-Based Spatial Analysis : Case Study Suoh Caldera Geopark, West Lampung - Bantjin, Theo Sampit Mo Rizky; Purnama, Yapi; Muhammad Athar Zidani; Harbowo, Danni Gathot (Department of Geography Education, University of Jember, 2026)
The Suoh Caldera Geopark area in West Lampung has an interesting geological setting characterized by diverse volcanic landforms, active fault systems, and distinctive geothermal phenomena. These geological characteristics reflect complex interactions between tectonic activity and volcanic processes that have shaped the regional landscape. To support the development of the Suoh Caldera Geopark as one of the UNESCO Global Geoparks in Indonesia, comprehensive geodiversity mapping strategy is required to identify and verify important geological values within the region. Therefore, this study aims to identify and map geodiversity hotspots using spatial analysis approach to determine areas with the most significant geological diversity. Research applies grid-based spatial indexing method using geodiversity measurements to identify locations with potential geodiversity in West Lampung. Total 111 grids were analyzed based on five main parameters: slope gradient, geological formations, drainage systems, topography, and geological structures, which were validated through field surveys. The spatial distribution geodiversity values further analyzed using the Inverse Distance Weighted interpolation method to identify areas with high geodiversity concentration. Results reveal five significant geodiversity hotspots: Sukausite (104°1'24